2011
DOI: 10.1002/mds.23469
|View full text |Cite
|
Sign up to set email alerts
|

The motor phenotype of Parkinson's disease in relation to age at onset

Abstract: This study highlights the clinical differences between early and late onset PD, which have important implications for diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
92
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 21 publications
8
92
1
2
Order By: Relevance
“…32,34 The LIDs and non-LIDs groups of our PD cohort were clinically different (so that reached statistical significance) for sex, age, disease duration, the duration on dopaminergic medication, and LED Total . We performed separate analysis corrected for sex and found similar but less significant results compared to our whole cohort (male and female).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…32,34 The LIDs and non-LIDs groups of our PD cohort were clinically different (so that reached statistical significance) for sex, age, disease duration, the duration on dopaminergic medication, and LED Total . We performed separate analysis corrected for sex and found similar but less significant results compared to our whole cohort (male and female).…”
mentioning
confidence: 85%
“…Previous studies looking for clinical risk factors in LIDs have shown that the occurrence of LIDs is linked with younger age at onset of PD, [31][32][33] as well as with longer disease duration. 32,34 The LIDs and non-LIDs groups of our PD cohort were clinically different (so that reached statistical significance) for sex, age, disease duration, the duration on dopaminergic medication, and LED Total .…”
mentioning
confidence: 99%
“…9 However, evidence supporting an influence of age on PD phenotype at its onset is lacking and conflicting. [10][11][12][13][14][15][16][17][18] Previous studies have poorly assessed the full spectrum of motor and nonmotor symptoms and they have not evaluated the relationship between PD phenotype and imaging and nonimaging biomarkers. The Parkinson's Progression Markers Initiative (PPMI) is an ongoing, international, multicenter, prospective study designed to discover and validate biomarkers of disease progression in newly diagnosed, drug-naive patients with PD.…”
mentioning
confidence: 99%
“…Parkinson disease (PD) is a degenerative and progressive disorder that mainly affects older people [1]. The rapid population ageing throughout developed countries means that the number of people diagnosed with PD will increase to over 10 million by 2050 [2].…”
Section: Introductionmentioning
confidence: 99%